Hedonic and utilitarian motivations and their relationship with cultural dimensions, life satisfaction and the attributes of supermarkets: An international study on consumer behavior - Rodrigo Ribeiro Coimbra; Carlos Melo Brito; Danilo de Oliveira Sampaio (Cogent Business & Management, 2023)
This research focuses on how consumers behave when they shop in supermarkets. It aims at understanding the relationship between hedonic and utilitarian motivations, cultural dimensions and satisfaction with life in context. Most researchers have studied how motivations and cultural dimensions affect consumer behavior. However, the studies conducted so far do not address the relationship between hedonic and utilitarian motivations, culture, satisfaction with life, and supermarket attributes. This research is mainly exploratory in nature and is based on three samples collected in different continents: Brazil, South Korea and Portugal. Evidence is found that satisfaction with life impacts utilitarian motivation but does not impact hedonic motivation. The study also shows that consumers satisfied with their life tend to be more rational in their purchases. Concerning the cultural dimension, power distance is the unique variable that positively impacts hedonic motivation, while long-term orientation has a negative impact on hedonic motivation. On the other hand, avoiding uncertainty and long-term orientation positively impact utilitarian behavior. Regarding the supermarkets' attributes, the study puts in evidence the significant positive impact of pricing policy, variety and quality of products, environment, service, and corporate social responsibility in the hedonic motivation.
Keywords: 650; Brazil; buying behavior; exploratory study; Marketing; Portugal; South Korea